Manajemen Strategi Pemasaran Produk Manulife Saving Protector pada PT Asuransi Jiwa Manulife Surabaya Pusat - Ananda Putri Kartika Dewi; I Gede Wiyasa MS (Universitas 45 Surabaya, 2024)
One of the best insurance companies in Indonesia is PT Asuransi Jiwa Manulife Indonesia, a financial services provider from Canada that operates in Asia, Canada and the United States. Headquartered in Toronto, Canada, Manulife has been serving customers for more than 155 years. Manulife is traded under the symbol ‘MFC’ on the Toronto, New York and Philippine stock exchanges, and under the symbol ‘945’ in Hong Kong. Manulife Indonesia has offered a variety of financial services including life insurance, accident and health insurance, investment services and pension funds to individual customers and business actors in Indonesia. Manulife Indonesia has served more than 2 million customers in Indonesia through a network of more than 11,000 employees and professional agents spread across 30 marketing offices. Given the increasing market potential in Indonesia, many insurance companies, both local and foreign, are trying to reach the market in Indonesia. In order for the company to be able to compete with other insurance companies, a sales strategy and product are needed that can attract the interest of its customers. One of the most popular products owned by PT AJ Manulife Indonesia is Manulife Saving Protector, which is the only individual dual-purpose life insurance product (endowment) that can provide Insurance Money of up to IDR 1.5 billion without having to undergo a medical examination first. The insurance industry in 2023 is projected to increase along with improving economic conditions in Indonesia. However, the level of public distrust can hinder the development of this industry. This causes many people to tend to delay opening an insurance policy.